Education on Prevention of Bullying Behavior: Eradicating the Seeds of Bullying in Elementary School Students - Setyastuti, Yuanita; Fahrianoor, Fahrianoor; Kumalawati, Rosalina; Yuliarti, Astinana; Hidayat, Muhammad Nizar (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2024)
This program was implemented at SDN Belitung Utara 3 Banjarmasin to provide education on bullying behavior to students and teachers. The aim of the program was to improve understanding related to bullying, its types, its impact, and prevention strategies. The program was conducted in several stages: (1) pre-test to measure students' initial knowledge, (2) education through socialization covering the understanding of bullying and preventive actions, (3) post-test to evaluate students' improved understanding after the socialization, and (4) program sustainability through the installation of "STOP BULLYING" educational posters in the school environment. Evaluation results showed a 26.08% increase in students' knowledge regarding types of bullying and how to deal with it. This improvement reflects the program's effectiveness in raising awareness among students and teachers about the importance of preventing bullying behavior. Although there were some challenges, such as limited program scope and budget constraints, this success provides a strong foundation for further efforts to reduce bullying incidents in elementary schools. The continuation of education through visual media is expected to continuously remind students and teachers of the importance of preventing bullying and creating a safe and positive learning environment. Program Dosen Wajib Mengabdi (PDWA) ini dilaksanakan di SDN Belitung Utara 3 Banjarmasin untuk memberikan edukasi mengenai perilaku perundungan (bullying) kepada siswa dan guru. Kegiatan ini bertujuan untuk meningkatkan pemahaman terkait bullying, jenis-jenisnya, dampak yang ditimbulkan, serta strategi pencegahannya. Pelaksanaan program dilakukan dalam beberapa tahap: (1) pre-test untuk mengukur pengetahuan awal siswa, (2) edukasi dalam bentuk sosialisasi yang mencakup pemahaman tentang bullying dan tindakan pencegahannya, (3) post-test untuk mengevaluasi peningkatan pemahaman siswa setelah sosialisasi, dan (4) keberlanjutan program melalui pemasangan poster edukasi "STOP BULLYING" di lingkungan sekolah. Hasil evaluasi menunjukkan adanya peningkatan pengetahuan siswa sebesar 26,08% terkait jenis-jenis bullying dan cara menghadapinya. Peningkatan ini menunjukkan efektivitas program dalam meningkatkan kesadaran siswa dan guru mengenai pentingnya mencegah perilaku perundungan. Meskipun terdapat beberapa kendala, seperti keterbatasan cakupan program dan dana yang terbatas, keberhasilan ini memberikan fondasi yang kuat untuk pengembangan lebih lanjut dalam mengurangi angka bullying di sekolah dasar. Keberlanjutan edukasi melalui media visual diharapkan dapat terus mengingatkan siswa dan guru akan pentingnya mencegah bullying dan menciptakan lingkungan belajar yang aman dan positif.